2012
DOI: 10.1038/gt.2012.82
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of triplex-forming PNA and donor DNA by nanoparticles mediates site-specific genome editing of human hematopoietic cells in vivo

Abstract: In vivodelivery is a major barrier to the use of molecular tools for gene modification. Here we demonstrate site-specific gene editing of human cells in vivo in hematopoietic stem cell-engrafted NOD-scid IL2rγnull mice, using biodegradable nanoparticles loaded with triplex-forming peptide nucleic acids (PNAs) and single-stranded donor DNA molecules. In vitro screening showed greater efficacy of nanoparticles containing PNAs/DNAs together over PNA-alone or DNA-alone. Intravenous injection of particles containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
108
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 36 publications
4
108
0
Order By: Relevance
“…[9][10][11][12] Additionally, the delivery of peptide nucleic acids by poly(lactic-co-glycolic acid) NPs for genome editing in HSCs is currently under investigation. 13,14 With the available knowledge, limited attention has been paid to the loading behavior of HSCs and HPCs with NPs, not to mention the kinetics involved. Since this determines the efficacy and safety of nanotechnology-based applications, it is definitely worthwhile to consider these aspects in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Additionally, the delivery of peptide nucleic acids by poly(lactic-co-glycolic acid) NPs for genome editing in HSCs is currently under investigation. 13,14 With the available knowledge, limited attention has been paid to the loading behavior of HSCs and HPCs with NPs, not to mention the kinetics involved. Since this determines the efficacy and safety of nanotechnology-based applications, it is definitely worthwhile to consider these aspects in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these complexes can be used to deliver therapeutic peptides or RNA in addition to conventional gene transfer via DNA. Notably, it has been demonstrated that nanoparticles can mediate in vivo gene editing by simultaneously delivering both the gene editing agent and a suitable donor template [ 155 ]. Thus, non-viral methods may be a promising method to deliver short bursts of gene editing drugs .…”
Section: In Vivo Correction By Direct Delivery Of Genome Editing Toolsmentioning
confidence: 99%
“…17 Silica nanoparticles have been linked to PNA by disulfide bond to achieve delivery and release of antisense PNAs in HeLa cells; 18 biodegradable PLGA formulations have been successfully employed for the delivery in vivo of PNA−polylysine conjugates in hematopoietic cells. 19 The main drawback of the cited strategies derives from the need of synthesizing special building blocks to be used in the solid phase synthesis or to conjugate the carriers on solid phase or in solution, ending up in very large molecules.…”
Section: ■ Introductionmentioning
confidence: 99%